Assessment of needs for counseling after prenatal diagnosis of congenital heart disease: a multidisciplinary approach = Pränatale Diagnostik angeborener Herzfehler : welche Parameter sind entscheidend für eine zufriedenstellende Aufklärung der Eltern? - Kovacevic, Alexander; Simmelbauer, Andreas; Starystach, Sebastian; Elsässer, Michael; Sohn, Christof; Bär, Stefan; Gorenflo, Matthias (Klinische Pädiatrie, 2018)
Background Congenital heart disease is the most common cause of major congenital anomalies. After prenatal diagnosis effective counseling is crucial. However, little research has been undertaken in determining the most effective techniques. Objectives To develop a questionnaire suitable to assess parental needs for counseling. Material and Methods A questionnaire was developed by pediatric cardiologists, maternal-fetal-medicine specialists and sociologists. Likert scaled and open-ended questions are combined with socio-demographical data. The questionnaire was prospectively pilot-tested on 17 parents. We present first analyses of n=41 parents. Results Response rate was 89.5%. The dependent variable “effective counseling” was measured in 5 dimensions (transfer of medical information, trust in medical staff, transparency of treatment process, coping resources and perceived situational control). The questionnaire’s internal consistency is high (Cronbach’s alpha>0.7). First analyses show that 44.7% perceived counseling as successful. Transfer of medical information seems difficult (36.6% success rate). Trust in medical staff was high with 75%. Conclusions This newly developed tool measures counseling success in five dimensions. A multidisciplinary approach is recommended as methodological expertise is essential for constructing adequate tests. Preliminary data indicate that transfer of medical information is not easily achieved. Further analyses are needed to identify factors that determine counseling success.